DIFFERENT FACADES OF PTH-DEPENDENT HYPERCALCEMIA IN PREGNANCY - Lee, Qin Zhi; Tee, Hwee Chin; Hii, Ling Yen (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Hypercalcemia is a rare occurrence during pregnancy. This can present variably and pose unique challenges in management. The general diagnostic approach is similar to the non-pregnant population however, additional considerations must be taken regarding the modality of investigations and safe treatment options during pregnancy. We present 3 pregnant patients who had PTH-dependent hypercalcemia. We explore their clinical presentation, diagnostic evaluation, management, and outcomes. Through this case series, we aim to highlight different aspects of management for hypercalcemia during pregnancy. CASE 1 A 32-year-old patient at 33 weeks period of gestation (POG) presented with acute pancreatitis and was found to have hypercalcemia 2.99 mmol/L and raised iPTH 16.64 pmol/L (reference range 1.59 - 7.24). Calcium levels showed a decreasing trend with hydration alone and the patient had an uneventful delivery at term. Postpartum calcium: creatinine clearance ratio (CCCR) of 0.02 confirmed primary hyperparathyroidism. Further evaluation was planned, however she defaulted on follow-up. CASE 2 A 37-year-old patient at 15 weeks POG presented with renal impairment due to nephrolithiasis, with severe hypercalcemia 3.9 mmol/L and elevated iPTH 162.4 pmol/L. Ultrasonography of the neck showed a left lower pole parathyroid lesion measuring 1.9 x 2.3 x 2.4 cm. Hypercalcemia was refractory to hydration and required calcitonin, cinacalcet and pamidronate. Leftfocused parathyroidectomy was performed at 17 weeks POG. Calcium levels normalized postoperatively. Histopathological examination confirmed parathyroid adenoma. Unfortunately, the patient opted for termination of pregnancy due to worsening renal function. CASE 3 A 31-year-old patient was diagnosed with Familial Hypocalciuric Hypercalcemia (FHH), evidenced by mild hypercalcemia 2.8 mmol/L, elevated iPTH 8.2 pmol/L, CCCR <0.01, and normal Vitamin D levels. There was worsening hypercalcemia at 2.98 mmol/L during pregnancy which improved with hydration. The pregnancy then continued uneventfully. Conclusion Hypercalcemia is rare in pregnancy, but its treatment necessitates a delicate balancing act to ensure the safety of both mother and offspring. Treatment must be given in a timely manner, and reassurance has to be provided to patients with benign conditions such as FHH.